Pre-treatment of seeds and planting: Transport of seedlings - International Livestock Research Institute (International Livestock Research Institute, 2010)
This video was made to document best practices for use in crop genebanks as part of a project on management of crop diversity as a global public good under the System-wide Genetic Resources Programme of the Consultative Group on International Agricultural Research. It was filmed and produced at the International Livestock Research Institute in Ethiopia by Lieven Corthouts with guidance and commentary provided by Alexandra Jorge and Jean Hanson and reviewed by Ehsan Dulloo and Imke Thormann.